The Study of Job Satisfaction of Employment Guidance Teachers in Heilongjiang International University in China - Wang, Qiushi (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
In recent years, the employment guidance teachers in private colleges and universities in China have grown rapidly. Whether they can be attracted and retained, and whether stimulate their work vitality, job satisfaction is an important indicator. The study found that the overall job satisfaction of employment guidance teachers is low and their turnover intention is high. This article investigated the job satisfaction of employment guidance teachers in Heilongjiang International University (HIU), using a quantitative questionnaire. According to the survey results of 200 respondents, various influencing factors are found, and the factors affecting the job satisfaction of employment guidance teachers are determined. Multiple regression analysis was used in this study. The results show that work load, work salary, interpersonal relationship and position promotion have a significant impact on job satisfaction.